BEYOND PURCHASE DECISIONS: UNDERSTANDING THE DRIVERS OF CONSUMER BOYCOTT INTENTIONS IN MALAYSIA - Fardhila Syahira Salmi Nordin; Nor Rahimy Khalid; Rozila Hassan (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
The continuous international conflict between Palestine-Israel has prompted calls for boycott against for goods and services or brands perceived to be alleged ties or supporting Israel. This study investigates the determinants of consumer boycott intentions in Malaysia, employing the Theory of Planned Behaviour (TPB) as a theoretical framework. A survey of 229 Malaysian consumers was conducted to examine how attitudes, subjective norms, and perceived behavioural control influence intentions to boycott products and services perceived to have connections with Israel. Additionally, the study explores the relationship between boycott intentions and actual purchase behaviour. Structural equation modeling reveals that attitudes (β = 0.688, p < 0.01) and perceived behavioural l control (β = 0.153, p < 0.01) positively influence boycott intentions, while subjective norms do not have a significant effect. Contrary to expectations, no significant relationship was found between boycott intentions and actual purchase behaviour. The model explains 72.7% of the variance in boycott intentions, demonstrating the TPB’s efficacy in understanding consumer boycotts within the Malaysian context.